2006
DOI: 10.1038/sj.cdd.4402027
|View full text |Cite
|
Sign up to set email alerts
|

TWEAK shall inherit the earth

Abstract: Sometimes size really does not matter: recent papers on the tumour necrosis factor (TNF)-like ligand, TWEAK (tumour necrosis factor-like weak inducer of apoptosis), and its diminutive 129 amino-acid receptor, FN14 (fibroblast growth factor (FGF) -inducible 14 kDa protein), describe an impressive and potent range of biological effects. The TNF superfamily (TNSF) receptor FN14 has a small cytoplasmic domain, and the limited similarity of its extracellular domain to the cysteine-rich domains of the TNFSF receptor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
22
0
4

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 28 publications
(43 reference statements)
0
22
0
4
Order By: Relevance
“…The range of activities of the TWEAK/Fn14 system and the tissue damage/injury-associated expression pattern of Fn14 argue for a role of TWEAK and Fn14 in wound healing, tissue repair, regeneration, and maintenance of tissue homeostasis. 11 In line with this, it has been found that TWEAK and Fn14 are required for the regenerative responses occurring after muscle injury, partial hepatectomy, and partial pancreatectomy. [12][13][14] In the case of exaggerated or chronic activation, however, the TWEAK/Fn14 system may also contribute to tissue injury.…”
Section: Introductionmentioning
confidence: 70%
“…The range of activities of the TWEAK/Fn14 system and the tissue damage/injury-associated expression pattern of Fn14 argue for a role of TWEAK and Fn14 in wound healing, tissue repair, regeneration, and maintenance of tissue homeostasis. 11 In line with this, it has been found that TWEAK and Fn14 are required for the regenerative responses occurring after muscle injury, partial hepatectomy, and partial pancreatectomy. [12][13][14] In the case of exaggerated or chronic activation, however, the TWEAK/Fn14 system may also contribute to tissue injury.…”
Section: Introductionmentioning
confidence: 70%
“…TWEAK is capable of inducing a number of diverse cell functions, including proliferation, differentiation, migration, and cell death, depending on cellular context (3,5,7). The ability of TWEAK to induce apoptosis in certain cells has been perplexing, given that its cognate receptor, FN14, lacks a cytoplasmic death domain.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent studies revealed that TWEAK activates a number of additional cellular functions including proliferation, differentiation, and migration (3)(4)(5)(6)(7). TWEAK is expressed in a variety of tissues and by certain types of immune cells and cancer cell lines.…”
mentioning
confidence: 99%
“…Strategies that could be useful for therapeutic targeting of this axis will also be discussed. The reader is referred to recent review articles by Vince and Silke 16 and Burkly et al 17 for additional information on the TWEAK-Fn14 axis and other perspectives on its likely function in normal and diseased tissues.…”
mentioning
confidence: 99%